Bidirectional associations between eosinophils, basophils, and lymphocytes with atopic dermatitis: A multivariable Mendelian randomization study - Zeng-Yun-Ou, Zhang; Zhong-Yu, Jian; Wei, Li (Frontiers in Immunology, 2022)
Background: Many previous clinical observational studies highlighted that the critical role of basophils, eosinophils and lymphocytes in AD. But, observational epidemiological designs are prone to reverse causation and unmeasured confounding. Whether basophils, eosinophils and lymphocytes have causal roles in the development of AD remain uncertain. Methods: Data on the large publicly available genome-wide association study (GWASs) related to immune cells were obtained from the UK Biobank and the Blood Cell Consortium with more than 500,000 subjects of European ancestry. The GWASs data for AD were from the three independent cohorts with more than 700,000 subjects of European ancestry. We performed single-variable Mendelian randomization (SVMR) followed by multivariable Mendelian randomization (MVMR) to assess the total and direct effects of these immune cells count on AD risk. Results: The SVMR estimates showed that genetically predicted higher eosinophil (OR: 1.23, 95% CI: 1.17–1.29, p = 5.85E−16) and basophil count levels (OR: 1.11, 95% CI: 1.03–1.19, p = 0.004) have an adverse effect on the risk of AD. On the contrary, higher lymphocyte count (OR: 0.93, 95% CI: 0.89–0.98, p = 0.006) decreased the risk of AD. For reverse MR analysis, patients with AD showed a higher level of basophil count (beta:0.04, 95% CI: 0.01–0.07, p = 0.014) and lower levels of lymphocyte count (beta: -0.05 95% CI: -0.09 – -0.01, p = 0.021). In MVMR, the effect of eosinophil (OR: 1.19, 95% CI: 1.09–1.29, p = 8.98E−05) and basophil count (OR: 1.19, 95% CI: 1.14–1.24, p = 3.72E−15), basophil (OR: 1.19, 95% CI: 1.14–1.24, p = 3.72E−15), and lymphocyte (OR: 0.93, 95% CI: 0.89–0.98, p = 0.006) count on AD were still significant. Conclusions: Our MR findings suggest that increasing the count of eosinophil and basophil cells and decreasing the count of lymphocytes are potential causal risk factors for AD independent of each other.